2005
DOI: 10.1111/j.1365-2419.2005.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating movement and abundance of Atka mackerel (Pleurogrammus monopterygius) with tag–release–recapture data

Abstract: A mark-recapture experiment was conducted in Seguam Pass, Alaska, to estimate local Atka mackerel (Pleurogrammus monopterygius) abundance and to evaluate the efficacy of trawl exclusion zones around Steller sea lion (Eumetopias jubatus) rookeries. Atka mackerel were found in dense aggregations near the Aleutian Islands where they are a major prey item of endangered Steller sea lions. In 1999, 1375 tagged fish were released and a biomass of 76 679 metric tonnes (t) was estimated outside a trawl exclusion zone u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…3 Relationship between distance moved per month and growth increment deviation calculated as ln(ΔL/Δ b L), where ΔL is the observed growth increment and Δ b L is the expected growth increment obtained from the von Bertalanffy growth models M 1 (see Table 1), for male and female sablefish. Regression line, growth increment deviation=0.28 log (movement distance + 1) -0.30, r=0.18 movement (Hunt et al 1999;McDermott et al 2005), but little is known about the sex-biased dispersal patterns in fishes. Beamish and McFarlane (1988) indicated that adult sablefish show little movement behavior, but our long-term data indicate that adult sablefish undergo long-distance movement.…”
Section: Discussionmentioning
confidence: 99%
“…3 Relationship between distance moved per month and growth increment deviation calculated as ln(ΔL/Δ b L), where ΔL is the observed growth increment and Δ b L is the expected growth increment obtained from the von Bertalanffy growth models M 1 (see Table 1), for male and female sablefish. Regression line, growth increment deviation=0.28 log (movement distance + 1) -0.30, r=0.18 movement (Hunt et al 1999;McDermott et al 2005), but little is known about the sex-biased dispersal patterns in fishes. Beamish and McFarlane (1988) indicated that adult sablefish show little movement behavior, but our long-term data indicate that adult sablefish undergo long-distance movement.…”
Section: Discussionmentioning
confidence: 99%
“…, 2005; Logerwell et al. , 2005; McDermott et al. , 2005), the biology and ecology of sea lions (Call and Loughlin, 2005; Fadely et al.…”
Section: Introductionmentioning
confidence: 99%
“…Adult Atka mackerel do not appear to be highly migratory (McDermott et al 2005), but the highly protracted spawning-brooding reproductive cycle (up to 6 months) and planktonic larval phase (up to 1 year), combined with vigorous current systems in the Gulf of Alaska and Bering Sea, suggest that long-distance dispersal is likely (Gorbunova 1962;Kendall and Dunn 1985) to impede genetic divergence. The Alaskan populations examined in the present study inhabit two major current systems that are partially isolated by the Alaska Peninsula and Aleutian Islands chain.…”
Section: Contemporary Genetic Population Structurementioning
confidence: 99%
“…Newly hatched larvae are neustonic (Kendall and Dunn 1985) and develop in pelagic habitats for 1 year before recruiting into demersal populations as juveniles. Tagging results indicate that adults form local aggregations and generally move less than 70 km (McDermott et al 2005).…”
mentioning
confidence: 99%